Performance Indicators for A Healthcare Company in Indonesia - Nugroho, Bangkit Puri; Wicaksono , Raden Danisworo Rivianto; Gustaji, Rhamdalia Fanny (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Indonesia's healthcare industry boasts a thriving pharmaceutical sector with revenue exceeding $9 billion. However, it faces a critical challenge. The infrastructure, with only 1.17 hospital beds per thousand inhabitants, struggles to meet the growing demand fueled by the rapid expansion of the JKN program, which now covers over 200 million participants. To address this challenge, this research proposes a Knowledge Based Performance Management Systems (KBPMS) framework, tailored for the healthcare sector. The framework encompasses 29 Key Performance Indicators (KPIs) categorized into three perspectives: Business Result, Internal Business Process, and Resource Capability. These KPIs provide a comprehensive and balanced assessment of healthcare organizations' performance across critical dimensions. Analysis of the proposed KPIs reveals that hospitals prioritize organizational development, emphasizing the importance of teamwork, knowledge sharing, and leadership skills among staff. These factors are crucial for fostering a collaborative and innovative work environment, enabling hospitals to deliver high-quality care and adapt to the evolving healthcare landscape. The KBPMS framework offers a valuable tool for healthcare organizations to enhance their performance management practices. By adopting this framework, hospitals can effectively measure, monitor, and improve their operations, leading to better patient outcomes and organizational sustainability. The research highlights the KBPMS framework's potential in Indonesia, but further research is needed to explore its effectiveness in broader healthcare settings and its long-term impact.